PENGARUH PEMBERIAN PUPUK KANDANG AYAM DAN ZAT PENGATUR TUMBUH GIBERELIN TERHADAP PERTUMBUHAN BIBIT KOPI ARABIKA (Coffea arabica L.) - Sitanggang, Asbon; Saputra, Sukemi Indra; ', Islan (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
This Researh aims to determine the effect of chicken manure and plant growth regulator of giberelin and good dose on the growth coffee arabika seeds. Research was conducted at the experimental farm of Agriculture Faculty, University of Riau from May to August 2014. This research utilized Split Plot Design, consist of 2 factors. The first factor, consentration of plant growth regulator as main plot were: without plant growth regulator, consentration 20 ppm and consentration 60 ppm. The second factor, chicken manure as sub plot were: without chicken manure, chiken manure 15 g/plant (10 ton/ha), chicken manure 22.5 g/plant (15 ton/ha), chicken manure 30 g/plant (20 ton/ha). The treatment with 3 replications and every replication with 3 units seeds so obtained 108 units experiment. Parameters observed were the increase of seeds height, leaves number, total wide of leaves seeds, root volume and root crown ratio. Data were analyzed using Analysis of Variance (ANOVA). The data obtained were further tested by Least Significant Diference (LSD) at the level 5 %. Based on the result it can be concluded that is not apparent after a statistical analysis on the parameters except the total wide of leaves seeds. Giving chicken manure at the dose of 30 g/plant (20 ton/ha) and plant growth regulator of giberelin 60 ppm has not followed the maximum result in all parameters tested. Keywords: chicken manure, plant growth regulator, giberelin, coffee arabica